Manganese-based polyanionic positive electrode material as well as preparation method and application thereof

By introducing lithium ions and optimizing the chemical structure, the problems of Jahn-Teller distortion and manganese element dissolution in manganese-based polyanionic cathode materials are solved, and the cycle stability and rate performance of the material are significantly improved.

CN119447286AActive Publication Date: 2025-02-14HARBIN UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411584474.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

In applications, manganese-based polyanionic cathode materials have Jahn-Teller distortion and manganese element dissolution, resulting in poor cycle stability, poor rate performance and low energy density.

Method used

Using a manganese-based polyanionic positive electrode material with the chemical formula NaxLiyMnV0.5Ti0.5(PO4)3, by introducing lithium ions, it weakens the overlap of the electron orbits of oxygen atoms and alkali metal ions, and enhances the Mn-O bond, thereby inhibiting Jahn-Teller. distortion.

Benefits of technology

It significantly improves the circulation stability and rate performance of the material, ensures the specific capacity of sodium storage, and reduces the defect formation rate and material distortion and dissolution problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447286A_ABST
    Figure CN119447286A_ABST
Patent Text Reader

Abstract

The invention discloses a manganese-based polyanionic positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of sodium-ion battery positive electrode materials. The chemical formula of the positive electrode material is NaxLiyMnV0. 5Ti0. 5 (PO4) 3, x is greater than or equal to 3 and less than or equal to 3.5, y is greater than or equal to 0 and less than or equal to 0.5, and x + y is equal to 3.5. As lithium ions are introduced, electron orbital overlap between alkaline metal ions and oxygen atoms is weakened, so that the oxygen atoms and surrounding Mn < 2 + > generate a stronger coordination effect, and the lithium ion battery can be used as a lithium ion battery. The enhanced Mn-O bond inhibits Jahn-Teller distortion caused by Mn < 3 + > (Mn < 2 + > is obtained by oxidizing at high potential) in the charging and discharging process; according to the manganese-based polyanionic positive electrode material, the cycling stability and the rate capability of the material can be remarkably improved while the sodium storage specific capacity is ensured, and the sodium storage electrochemical performance of the manganese-based polyanionic positive electrode material is obviously superior to that of a lithium-free pure-phase material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a manganese-based polyanion positive electrode material and a preparation method and application thereof. Background Art

[0002] With the transformation of the global energy structure and the demand for sustainable development, it is particularly important to develop efficient, low-cost, and environmentally friendly energy storage technologies. Among various energy storage technologies, lithium-ion batteries have become a research hotspot in recent years due to their advantages such as high energy density, long cycle life, and fast charging and discharging. However, due to the high cost of lithium-ion batteries and the scarcity and difficulty of domestic lithium metal resources, it is urgent to research and develop a new generation of secondary batteries with higher performance, longer life, economy, and safety. Compared with lithium metal, sodium metal resources are abundant and inexpensive. At the same time, thanks to the similar chemical properties of sodium and lithium, sodium-ion batteries have become a new choice in secondary batteries.

[0003] The cathode material plays a key role in sodium-ion batteries, not only because of its high specific gravity, but more importantly, it determines the operating voltage range of the battery. An ideal cathode material should have the characteristics of high operating voltage, large specific capacity, good electronic and ionic conductivity, structural stability, low cost and low toxicity. At present, the mainstream cathode materials in sodium-ion batteries are divided into: layered oxides, polyanionic compounds, Prussian blue materials, and other materials. Among them, polyanionic compounds have become a research hotspot in recent years due to their excellent cycle performance and rate performance, stable operating voltage platform, good ion conductivity, and very high thermal stability. Manganese has multivalent characteristics, and its abundant resources, low price, green and non-toxic characteristics make it one of the best choices for sodium-ion battery cathode materials. The development of a new generation of manganese-based polyanionic cathode materials with high capacity, green and low toxicity, safety and economy has become a research priority.

[0004] However, manganese-based polyanion cathode materials also face many challenges in their applications, such as short cycle life caused by Jahn-Teller distortion and dissolution of manganese, poor rate performance and low energy density caused by material antisite defects and low intrinsic conductivity of polyanion cathode materials. Seeking appropriate solutions to reduce the formation rate of defects and improve many problems such as poor energy density, short cycle life and poor rate performance is an urgent problem to be solved in this field. Summary of the invention

[0005] The purpose of the present invention is to provide a manganese-based polyanion positive electrode material and a preparation method and application thereof, so as to solve the technical problem that the existing manganese-based polyanion positive electrode materials have Jahn-Teller distortion and manganese element dissolution, resulting in poor cycle stability of the battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a manganese-based polyanion positive electrode material, wherein the chemical formula of the manganese-based polyanion positive electrode material is Na x Li y MnV 0.5 Ti 0.5 (PO4)3; Among them: 3≤x≤3.5, 0≤y≤0.5, x+y=3.5.

[0007] The present invention also discloses a method for preparing the above-mentioned manganese-based polyanion positive electrode material, comprising the following steps: According to the chemical formula Na x Li y MnV 0.5 Ti 0.5 The sodium salt, lithium salt, manganese salt, vanadium salt, titanium salt and phosphate are weighed in a stoichiometric ratio in (PO4)3, and then dissolved in a solvent together with a coupling agent as a raw material, and stirred and heated to obtain a mixed solution; The mixed solution is dried and ground in sequence to obtain a precursor powder; The precursor powder is sintered to obtain a manganese-based polyanion positive electrode material; The transition metal salts are manganese salts, vanadium salts and titanium salts.

[0008] Further, the sodium salt is one or more of sodium acetate trihydrate, sodium nitrate and sodium carbonate; the lithium salt is one or more of lithium acetate, lithium nitrate and lithium oxalate; the manganese salt is one or more of manganese nitrate tetrahydrate, manganese acetate and manganese acetate tetrahydrate; The molar ratio of the coupling agent to the metal ions in the transition metal salt is 1:1.

[0009] Further, the vanadium salt is one or more of ammonium metavanadate, vanadium acetylacetonate and vanadium pentoxide; the titanium salt is one or more of tetrabutyl titanate, isopropyl titanate and titanium tetrachloride; the phosphate is one or more of diammonium dihydrogen phosphate, phosphoric acid and diammonium hydrogen phosphate; The coupling agent is one or more of citric acid monohydrate, ascorbic acid and oxalic acid.

[0010] Furthermore, the titanium salt and vanadium acetylacetonate are water-insoluble salts; when they are water-insoluble salts, anhydrous ethanol is used as the solvent.

[0011] Further, the remaining vanadium salts and sodium salts, lithium salts, manganese salts, phosphates and coupling agents are all water-soluble salts; When the salt is water-soluble, deionized water is used as the solvent.

[0012] Furthermore, the usage ratio of the raw material to the solvent is 1 g: (14.87-19.06) mL.

[0013] Furthermore, the temperature of the heating and mixing is 80-90°C; and the temperature of the drying is 100-120°C.

[0014] Furthermore, the process parameters of the sintering treatment are: pre-sintering at a temperature of 350-450° C. for 1-6 hours, and then sintering at a temperature of 600-700° C. for 6-20 hours.

[0015] The invention also discloses the application of the manganese-based polyanion positive electrode material in the active material of the sodium ion battery electrode.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a manganese-based polyanion positive electrode material, the chemical formula of which is Na x Li y MnV 0.5 Ti 0.5 (PO4)3, where 3≤x≤3.5, 0≤y≤0.5, and x+y=3.5. Due to the introduction of lithium ions, the electron orbital overlap between the alkaline metal ions and the oxygen atoms is weakened, thereby making the oxygen atoms and the surrounding Mn 2+ This enhanced Mn-O bond suppresses the Mn-O bond in the charge and discharge process. 3+ (Mn 2+ Jahn-Teller distortion caused by oxidation at high potential); the manganese-based polyanion positive electrode material can significantly improve the cycle stability and rate performance of the material while ensuring the sodium storage capacity, and its sodium storage electrochemical performance is significantly better than that of pure phase materials without lithium doping.

[0017] Furthermore, by replacing lithium ions in different proportions at the sodium position of the material, the defect formation rate of the manganese-based polyanion material was effectively reduced, and the deformation and dissolution of the material were suppressed to a certain extent. At the same time, through traditional carbon coating technology, the problem of poor intrinsic conductivity of the material was improved, and the sodium ion migration ability, energy density and cycle stability of the positive electrode material were significantly improved.

[0018] Furthermore, according to relevant experimental results, the Na3Li prepared by the present invention 0.5 MnV 0.5 Ti 0.5 (PO4)3 shows significant advantages in operating voltage and energy density, and can operate stably at a high voltage of 4.3V, corresponding to an energy density of 513.8Wh / kg.

[0019] The present invention also discloses a method for preparing the above-mentioned manganese-based polyanionic positive electrode material, which is synthesized through a traditional sol-gel method and sintering treatment, using common sodium salts, lithium salts, manganese salts, vanadium salts, titanium salts, phosphates and coupling agents as raw materials. No harmful waste liquid is generated during the synthesis process, and the method has the advantage of low production cost. The sintering treatment temperature used in the preparation process usually does not exceed 700°C, the process is simple and easy, and is suitable for large-scale production.

[0020] Furthermore, the present invention also proposes an effective improvement method for the problems of anti-site defects, poor sodium storage performance and short cycle life of manganese-based polyanion positive electrode materials; that is, lithium ion substitution is performed at the sodium position, and this method can effectively reduce the defect formation rate, optimize the sodium ion migration path, and improve the Mn 3+ The distortion and dissolution phenomenon of the material can be eliminated, thereby greatly improving the cycle performance and rate performance of the material.

[0021] The present invention also discloses the application of the above-mentioned manganese-based polyanion positive electrode material in the active material of the sodium ion battery electrode. Due to the introduction of lithium ions, the material structure degradation and antisite defect phenomenon caused by manganese are improved, and the cycle stability and rate performance of the material are improved. In addition, the lithium-doped manganese-based polyanion positive electrode material uses green, economical and environmentally friendly manganese as the main transition metal. Therefore, the lithium-doped manganese-based polyanion positive electrode material with excellent electrochemical performance prepared by this patent has obvious advantages when used as the active material of the sodium ion battery electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD diagrams of the positive electrode materials prepared in Example 1, Example 3, Example 5 and Comparative Example 1; Figure 2 This is a SEM image of the positive electrode material prepared in Example 5; Figure 3 The manganese-based polyanion positive electrode material prepared in Example 1 was -1 The charge and discharge curves of the first three cycles under the current density; Figure 4 The manganese-based polyanion positive electrode material prepared in Example 1 was -1 Cyclic stability diagram for the first 60 cycles at the current density; Figure 5 The manganese-based polyanion positive electrode material prepared in Example 3 was -1 The charge and discharge curves of the first three cycles under the current density; Figure 6 The manganese-based polyanion positive electrode material prepared in Example 3 was -1 Cyclic stability diagram for the first 60 cycles at the current density; Figure 7 The manganese-based polyanion positive electrode material prepared in Example 5 was -1 The charge and discharge curves of the first three cycles under the current density; Figure 8 A comparison chart of the capacity cycle retention rate of the manganese-based polyanion positive electrode material prepared in Example 5; Fig. 9 This is a comparison chart of the rate performance of the manganese-based polyanion positive electrode material prepared in Example 5 and the positive electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0025] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0026] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0027] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0029] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0030] Example 1 A manganese-based polyanion positive electrode material (Na 3.4 Li 0.1 MnV 0.5 Ti 0.5 The preparation method of (PO4)3) comprises the following steps: According to the chemical formula Na 3.4 Li 0.1 MnV 0.5 Ti 0.5 The stoichiometric ratio in (PO4)3 is as follows: 0.568 g of isopropyl titanate is weighed and dissolved in 30 mL of anhydrous ethanol, and stirred for 30 min to obtain a solution containing isopropyl titanate; 1.44 g of sodium carbonate, 0.041 g of lithium oxalate, 1 g of manganese nitrate tetrahydrate, 0.364 g of vanadium pentoxide, 1.41 g of ascorbic acid and 1.18 g of phosphoric acid are weighed and dissolved in 70 mL of deionized water, and stirred for 30 min to obtain a solution containing sodium carbonate, lithium oxalate, manganese nitrate tetrahydrate, vanadium pentoxide, phosphoric acid and ascorbic acid; Under high-speed stirring (600 rpm), a solution containing isopropyl titanate was added dropwise to a solution containing sodium carbonate, lithium oxalate, manganese nitrate tetrahydrate, vanadium pentoxide, phosphoric acid and ascorbic acid to form a mixed solution, and the mixed solution was stirred and heated at 80° C. to obtain a mixed gel; The mixed gel was transferred into a constant temperature forced air oven at 100°C for drying, and then ground to obtain a precursor powder; The precursor powder was transferred to a tube furnace, and pre-calcined at 350°C for 3 hours and calcined at 650°C for 12 hours under the protection of an argon atmosphere. The obtained product was ground again to obtain a manganese-based polyanion positive electrode material.

[0031] Example 2 A manganese-based polyanion positive electrode material (Na 3.3 Li 0.2 MnV 0.5 Ti 0.5 The preparation method of (PO4)3) comprises the following steps: According to the chemical formula Na 3.3 Li 0.2 MnV0.5 Ti 0.5 (PO4)3, weigh 0.681g of tetrabutyl titanate and dissolve it in 30mL of anhydrous ethanol, stir for 30min to obtain a solution containing tetrabutyl titanate; weigh 1.8g of sodium acetate trihydrate, 0.056g of lithium nitrate, 0.692g of manganese acetate, 0.234g of ammonium metavanadate, 1.68g of citric acid monohydrate and 1.38g of ammonium dihydrogen phosphate and dissolve them in 70mL of deionized water, stir for 30min to obtain a solution containing sodium acetate trihydrate, lithium nitrate, manganese acetate, ammonium metavanadate, ammonium dihydrogen phosphate and citric acid monohydrate; Under high-speed stirring (600 rpm), a solution containing tetrabutyl titanate is added dropwise to a solution containing sodium acetate trihydrate, lithium nitrate, manganese acetate, ammonium metavanadate, ammonium dihydrogen phosphate and citric acid monohydrate to form a mixed solution, and the mixed solution is stirred and heated at 80° C. to obtain a mixed gel; The mixed gel was transferred into a constant temperature forced air oven at 100°C for drying, and then ground to obtain a precursor powder; The precursor powder was transferred to a tube furnace, and pre-calcined at 350°C for 3 hours and calcined at 650°C for 12 hours under the protection of an argon atmosphere. The obtained product was ground again to obtain a manganese-based polyanion positive electrode material.

[0032] Example 3 A manganese-based polyanion positive electrode material (Na 3.2 Li 0.3 MnV 0.5 Ti 0.5 The preparation method of (PO4)3) comprises the following steps: According to the chemical formula Na 3.2 Li 0.3 MnV 0.5 Ti 0.5 The stoichiometric ratio in (PO4)3 is as follows: 0.697 g of vanadium acetylacetonate is dissolved in 30 mL of anhydrous ethanol and stirred for 30 min to obtain a solution containing vanadium acetylacetonate; 1.09 g of sodium nitrate, 0.079 g of lithium acetate, 0.692 g of manganese acetate, 0.379 g of titanium tetrachloride, 0.72 g of oxalic acid and 1.59 g of diammonium hydrogen phosphate are dissolved in 70 mL of deionized water and stirred for 30 min to obtain a solution containing sodium nitrate, lithium acetate, manganese acetate, titanium tetrachloride, diammonium hydrogen phosphate and oxalic acid; Under high-speed stirring (600 rpm), a solution containing vanadium acetylacetonate is added dropwise to a solution containing sodium nitrate, lithium acetate, manganese acetate, titanium tetrachloride, diammonium hydrogen phosphate and polyvinyl pyrrolidone to form a mixed solution, and the mixed solution is stirred and heated at 80° C. to obtain a mixed gel; The mixed gel was transferred into a constant temperature forced air oven at 100°C for drying, and then ground to obtain a precursor powder; The precursor powder was transferred to a tube furnace, and pre-calcined at 350°C for 3 hours and calcined at 650°C for 12 hours under the protection of an argon atmosphere. The obtained product was ground again to obtain a manganese-based polyanion positive electrode material.

[0033] Example 4 A manganese-based polyanion positive electrode material (Na 3.1 Li 0.4 MnV 0.5 Ti 0.5 The preparation method of (PO4)3) comprises the following steps: According to the chemical formula Na 3.1 Li 0.4 MnV 0.5 Ti 0.5 (PO4)3, weigh 0.681g of tetrabutyl titanate and dissolve it in 30mL of anhydrous ethanol, stir for 30min to obtain a solution containing tetrabutyl titanate; weigh 1.687g of sodium acetate trihydrate, 0.106g of lithium acetate, 0.98g of manganese acetate tetrahydrate, 0.234g of ammonium metavanadate, 1.41g of ascorbic acid and 1.38g of ammonium dihydrogen phosphate and dissolve them in 70mL of deionized water, stir for 30min to obtain a solution containing sodium acetate trihydrate, lithium acetate, manganese nitrate tetrahydrate, ammonium metavanadate, citric acid monohydrate and ammonium dihydrogen phosphate; Under high-speed stirring (600 rpm), a solution containing tetrabutyl titanate was added dropwise to a solution containing sodium acetate trihydrate, lithium acetate, manganese nitrate tetrahydrate, ammonium metavanadate, citric acid monohydrate and ammonium dihydrogen phosphate to form a mixed solution, and the mixed solution was stirred and heated at 80° C. to obtain a mixed gel; The mixed gel was transferred into a constant temperature forced air oven at 100°C for drying, and then ground to obtain a precursor powder; The precursor powder was transferred to a tube furnace, and pre-calcined at 350°C for 3 hours and calcined at 650°C for 12 hours under the protection of an argon atmosphere. The obtained product was ground again to obtain a manganese-based polyanion positive electrode material.

[0034] Example 5 A manganese-based polyanion positive electrode material (Na3Li 0.5 MnV 0.5 Ti 0.5 The preparation method of (PO4)3) comprises the following steps: According to the chemical formula Na3Li 0.5 MnV 0.5 Ti 0.5(PO4)3, weigh 0.681g of tetrabutyl titanate and dissolve it in 30mL of anhydrous ethanol, stir for 30min to obtain a solution containing tetrabutyl titanate; weigh 1.633g of sodium acetate trihydrate, 0.138g of lithium nitrate, 0.98g of manganese acetate tetrahydrate, 0.234g of ammonium metavanadate, 1.68g of citric acid monohydrate and 1.38g of ammonium dihydrogen phosphate and dissolve them in 70mL of deionized water, stir for 30min to obtain a solution containing sodium acetate trihydrate, lithium nitrate, manganese nitrate tetrahydrate, ammonium metavanadate, citric acid monohydrate and ammonium dihydrogen phosphate; Under high-speed stirring (600 rpm), a solution containing tetrabutyl titanate was added dropwise into a solution containing sodium acetate trihydrate, lithium nitrate, manganese nitrate tetrahydrate, ammonium metavanadate, citric acid monohydrate and ammonium dihydrogen phosphate to form a mixed solution, and the mixed solution was stirred and heated at 80°C to obtain a mixed gel; The mixed gel was transferred into a constant temperature forced air oven at 100°C for drying, and then ground to obtain a precursor powder; The precursor powder was transferred to a tube furnace, and pre-calcined at 350°C for 3 hours and calcined at 650°C for 12 hours under the protection of an argon atmosphere. The obtained product was ground again to obtain a manganese-based polyanion positive electrode material.

[0035] Comparative Example 1 The difference from Example 3 is that the amount of salt added is different and no lithium salt is added. The remaining steps and parameters are the same as those in Example 3 to obtain a pure phase manganese-based polyanion sodium ion battery positive electrode material (Na 3.5 MnV 0.5 Ti 0.5 (PO4)3), the steps are as follows: Weigh 0.681 g of tetrabutyl titanate and dissolve it in 30 mL of anhydrous ethanol, and stir for 30 min; weigh 1.905 g of sodium acetate trihydrate, 0.98 g of manganese acetate tetrahydrate, 0.234 g of ammonium metavanadate, 1.68 g of citric acid monohydrate, and 1.38 g of ammonium dihydrogen phosphate and dissolve them in 70 mL of deionized water, and stir for 30 min; Under high-speed stirring (600 rpm), a solution containing tetrabutyl titanate was added dropwise to a solution containing sodium acetate trihydrate, manganese nitrate tetrahydrate, ammonium metavanadate, citric acid monohydrate and ammonium dihydrogen phosphate to form a mixed solution, and the mixed solution was heated and stirred at 80° C. until a gel was formed; The gel was transferred into a constant temperature forced air oven at 100° C. for drying, and then the thoroughly dried sample was ground to obtain the precursor powder; The precursor powder was transferred to a tube furnace, and pre-calcined at 350°C for 3 hours and calcined at 650°C for 12 hours under the protection of an argon atmosphere. The product was ground again to obtain a pure phase manganese-based polyanion positive electrode material.

[0036] Application Example 1 A method for preparing a button cell using the lithium-doped manganese-based polyanion material obtained in Example 1 as a positive electrode material comprises the following steps: The manganese-based polyanion positive electrode material (Na 3.4 Li 0.1 MnV 0.5 Ti 0.5 (PO4)3), conductive carbon black and binder polyvinylidene fluoride, weigh 0.7g, 0.2g and 0.1g respectively according to the mass ratio of 7:2:1, mix them, and evenly disperse them in N-methylpyrrolidone solvent, then evenly coat the obtained mixed slurry on aluminum foil, and dry it at 80°C for 6h to obtain the positive electrode sheet; Sodium metal and glass fiber (Whatman, GF / D) were used as counter electrode and separator, respectively. They were placed in a CR2032 button battery in the order of negative electrode shell, spring, gasket, counter electrode, separator, positive electrode sheet and positive electrode shell. An electrolyte with a concentration of 1 mol / L was added, using sodium hexafluorophosphate as solute, propylene carbonate as solvent and 5% fluoroethylene carbonate as additive. After packaging, a sodium ion button battery was obtained.

[0037] Application Example 2 The method for preparing a button cell using the lithium-doped manganese-based polyanion material obtained in Example 2 as a positive electrode material comprises the following steps: The manganese-based polyanion positive electrode material (Na 3.2 Li 0.3 MnV 0.5 Ti 0.5 (PO4)3), conductive carbon black and binder polyvinylidene fluoride, weigh 0.7g, 0.2g and 0.1g respectively according to the mass ratio of 7:2:1, mix them, and evenly disperse them in N-methylpyrrolidone solvent, then evenly coat the obtained mixed slurry on aluminum foil, and dry it at 80°C for 6h to obtain the positive electrode sheet; Sodium metal and glass fiber (Whatman, GF / D) were used as counter electrode and separator, respectively. They were placed in a CR2032 button battery in the order of negative electrode shell, spring, gasket, counter electrode, separator, positive electrode sheet and positive electrode shell. An electrolyte with a concentration of 1 mol / L was added, using sodium hexafluorophosphate as solute, propylene carbonate as solvent and 5% fluoroethylene carbonate as additive. After packaging, a sodium ion button battery was obtained.

[0038] Application Example 3 The method for preparing a button cell using the lithium-doped manganese-based polyanion material obtained in Example 3 as a positive electrode material comprises the following steps: The manganese-based polyanion positive electrode material (Na3Li 0.5 MnV 0.5 Ti 0.5 (PO4)3), conductive carbon black and binder polyvinylidene fluoride, weigh 0.7g, 0.2g and 0.1g respectively according to the mass ratio of 7:2:1, mix them, and evenly disperse them in N-methylpyrrolidone solvent, then evenly coat the obtained mixed slurry on aluminum foil, and dry it at 80°C for 6h to obtain the positive electrode sheet; Sodium metal and glass fiber (Whatman, GF / D) were used as counter electrode and separator, respectively. They were placed in a CR2032 button battery in the order of negative electrode shell, spring, gasket, counter electrode, separator, positive electrode sheet and positive electrode shell. An electrolyte with a concentration of 1 mol / L was added, using sodium hexafluorophosphate as solute, propylene carbonate as solvent and 5% fluoroethylene carbonate as additive. After packaging, a sodium ion button battery was obtained.

[0039] Application Example 4 The obtained pure-phase manganese-based polyanion positive electrode material was used in the same manner as in Application Example 3 to prepare a sodium ion button battery using the pure-phase manganese-based polyanion positive electrode material as the positive electrode material.

[0040] Figure 1 The XRD diagrams of the positive electrode materials prepared in Example 1, Example 3, Example 5 and Comparative Example 1 show that all four materials have obvious diffraction peaks and no impurity peaks, indicating that the four materials have high crystallinity and phase purity.

[0041] Figure 2 This is the SEM image of Example 5. It can be seen from the figure that the material is a nano-scale block particle with good crystallinity. At the same time, amorphous carbon is tightly wrapped on the surface of the particle and has good conductivity.

[0042] Figure 3 The manganese-based polyanion positive electrode material prepared in Example 1 was -1 The charge-discharge curves of the first three cycles under the current density show that the sodium-ion battery works stably in the voltage window of 1.5-4.3 V, and the first cycle discharge capacity is about 113.75 mAh g -1 , the charge and discharge curves of the first three cycles almost overlap, indicating its good charge and discharge reversibility.

[0043] Figure 4 The manganese-based polyanion positive electrode material prepared in Example 1 was -1The cyclic stability diagram of the first 60 cycles under current density shows that the material described in Example 1 has good cyclic stability at 100 mA g -1 The capacity retention rate was 83.6% after 60 cycles at a current density of .

[0044] Figure 5 The manganese-based polyanion positive electrode material prepared in Example 3 was -1 The charge-discharge curves of the first three cycles under the current density show that the sodium-ion battery works stably in the voltage window of 1.5-4.3 V, and the first cycle discharge capacity is about 110.12 mAh g -1 , the charge and discharge curves of the first three cycles almost overlap, indicating its good charge and discharge reversibility.

[0045] Figure 6 The manganese-based polyanion positive electrode material prepared in Example 3 was -1 The cyclic stability diagram for the first 60 cycles under current density shows that the material described in Example 2 has a good stability at 100 mA g -1 After 60 cycles at a current density of , the capacity retention rate was 67.7%.

[0046] Figure 7 The manganese-based polyanion positive electrode material prepared in Example 5 was -1 The charge-discharge curves of the first three cycles under the current density show that the sodium-ion battery works stably in the voltage window of 1.5-4.3 V, and the first cycle discharge capacity is about 98.8 mAh g -1 , the charge and discharge curves of the first three cycles almost overlap, indicating its good charge and discharge reversibility.

[0047] Figure 8 The capacity cycle retention rate comparison diagram of the manganese-based polyanion positive electrode material prepared in Example 5 shows that at 100 mA g -1 The capacity retention curve after 130 cycles at a current density of , from which we can see that the Na prepared in Example 5 3.5 MnV 0.5 Ti 0.5 (PO4)3 material has good cycle stability at 100mA g -1 After 130 cycles at a current density of , the capacity retention rate was 82.8%, while the Na prepared in Comparative Example 1 3.5 MnV 0.5 Ti 0.5 Under the same test conditions, the capacity retention rate of (PO4)3 material is only 49.5%.

[0048] Fig. 9The figure is a comparison of the rate performance of the manganese-based polyanion positive electrode material prepared in Example 5 and the positive electrode material of Comparative Example 1. It can be seen from the figure that the rate performance of the material is greatly improved by replacing the sodium position with lithium ions. At a current density of 20C, the Na prepared in Example 5 3.5 MnV 0.5 Ti 0.5 The discharge capacity of (PO4)3 material is about 52.83 mAhg -1 , while the Na prepared in Comparative Example 1 3.5 MnV 0.5 Ti 0.5 The discharge capacity of (PO4)3 material is only 7.28 mAh g -1 .

[0049] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A manganese-based polyanion positive electrode material, characterized in that: The chemical formula of the manganese-based polyanion positive electrode material is Na x Li y MnV 0.5 Ti 0.5 (PO4)3; Among them: 3≤x≤3.5, 0≤y≤0.5, x+y=3.

5.

2. The method for preparing a manganese-based polyanion positive electrode material according to claim 1, characterized in that: The following steps are involved: According to the chemical formula Na x Li y MnV 0.5 Ti 0.5 The sodium salt, lithium salt, manganese salt, vanadium salt, titanium salt and phosphate are weighed in a stoichiometric ratio in (PO4)3, and then dissolved in a solvent together with a coupling agent as a raw material, and stirred and heated to obtain a mixed solution; The mixed solution is dried and ground in sequence to obtain a precursor powder; The precursor powder is sintered to obtain a manganese-based polyanion positive electrode material; The transition metal salts are manganese salts, vanadium salts and titanium salts.

3. The method for preparing a manganese-based polyanion positive electrode material according to claim 2, characterized in that: The sodium salt is one or more of sodium acetate trihydrate, sodium nitrate and sodium carbonate; the lithium salt is one or more of lithium acetate, lithium nitrate and lithium oxalate; the manganese salt is one or more of manganese nitrate tetrahydrate, manganese acetate and manganese acetate tetrahydrate; The molar ratio of the coupling agent to the metal ions in the transition metal salt is 1:

1.

4. The method for preparing a manganese-based polyanion positive electrode material according to claim 3, characterized in that: The vanadium salt is one or more of ammonium metavanadate, vanadium acetylacetonate and vanadium pentoxide; the titanium salt is one or more of tetrabutyl titanate, isopropyl titanate and titanium tetrachloride; the phosphate is one or more of ammonium dihydrogen phosphate, phosphoric acid and diammonium hydrogen phosphate; The coupling agent is one or more of citric acid monohydrate, ascorbic acid and oxalic acid.

5. The method for preparing a manganese-based polyanion positive electrode material according to claim 2, characterized in that: The titanium salt and vanadium acetylacetonate are water-insoluble salts; when they are water-insoluble salts, anhydrous ethanol is used as the solvent.

6. The method for preparing a manganese-based polyanion positive electrode material according to claim 5, characterized in that: The remaining vanadium salts and sodium salts, lithium salts, manganese salts, phosphates and coupling agents are all water-soluble salts; When the salt is water-soluble, deionized water is used as the solvent.

7. The method for preparing a manganese-based polyanion positive electrode material according to claim 2, characterized in that: The usage ratio of the raw material to the solvent is 1 g: (14.87-19.06) mL.

8. The method for preparing a manganese-based polyanion positive electrode material according to claim 2, characterized in that: The temperature of the heating and mixing is 80-90°C; the temperature of the drying is 100-120°C.

9. The method for preparing a manganese-based polyanion positive electrode material according to claim 2, characterized in that: The process parameters of the sintering treatment are: pre-sintering at a temperature of 350-450° C. for 1-6 hours, and then sintering at a temperature of 600-700° C. for 6-20 hours.

10. Use of the manganese-based polyanion positive electrode material according to claim 1 in active materials for sodium ion battery electrodes.

Citation Information

Patent Citations

  • P2 type layered sodium ion battery positive electrode material and preparation method thereof

    CN113921809A

  • Modified vanadium manganese sodium phosphate positive electrode material and preparation and application thereof

    CN115498183A

  • Li / Cu co-doped layered manganese-based sodium ion battery positive electrode material as well as preparation method and application thereof

    CN116102068A

  • High-energy-density sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN118841572A

  • Preparation method of polyanionic composite material

    CN118851129A